Nursing car for Children with Electrolyte Imbalances - สุขเลิศตระกูล, ฐิติมา (Nursing Journal CMU, 2018)
Electrolyte imbalances are common in the hospitalized child. Hyponatremia and hypokalemia are most frequently electrolyte imbalances and are leading cause of morbidity and mortality from complications, especially neurological and cardiovascular complications. Caring for the hospitalized child with hyponatremia and hypokalemia, the nurse assumes the role of continuously monitoring for signs of complications and efficacy of treatments. The purpose of this article is to provide the knowledge and understanding for the nurse regarding hyponatremia and hypokalemia in children. The main issues are as follows: incidence, etiology, clinical manifestations, treatment, and nursing care, these can be used to plan appropriate care for children with hyponatremia or hypokalemia.